Kaderlid van het NVV-jc voor het distriktskantoor aan de Mathenesserlaan 302, Rotterdam - André de la Porte, R.
Kaderlid van het NVV-jc voor het distriktskantoor aan de Mathenesserlaan 302, Rotterdam.